2011
DOI: 10.1121/1.3588469
|View full text |Cite
|
Sign up to set email alerts
|

Flow and geometry induced scattering of high frequency acoustic duct modes.

Abstract: a b s t r a c tCut-on cut-off transition of acoustic modes in hard-walled ducts with irrotational mean flow is well understood for Helmholtz numbers of order unity. Previous finite-element simulations of this phenomenon, however, appear to indicate the possibility of energy scattering into neighbouring modes at moderately large Helmholtz numbers. In this paper, such scattering phenomena are explained and predicted in slowly varying aeroengine ducts using a multiple-scales approach. It is found that, for suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Such modifications include introduction of holes with sharp edges [2], barriers in the path of flow [3], or sudden contraction or expansion as is the case with the SEC [4]. Applications of this phenomenon in vortex motion have been successfully studied by Smith et al, [5] who identified two scattering mechanisms that allow neighbouring modes to interact; scattering occurs at significantly lower frequencies when the mean flow is present; an exchange of energy between mean flow and acoustic field occurs during scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Such modifications include introduction of holes with sharp edges [2], barriers in the path of flow [3], or sudden contraction or expansion as is the case with the SEC [4]. Applications of this phenomenon in vortex motion have been successfully studied by Smith et al, [5] who identified two scattering mechanisms that allow neighbouring modes to interact; scattering occurs at significantly lower frequencies when the mean flow is present; an exchange of energy between mean flow and acoustic field occurs during scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Boucheron et al [2] made a comprehensive review of axisymmetric acoustic wave propagating in the rigid-walled pipeline. In the case of a lined-walled pipeline where the effect of acoustic impedance of the wall was considered, theoretical and numerical contributions were made by Rienstra and Darau [3], Rienstra [14], Smith et al [15], Brambley et al [16], and Buske et al [17]. Some experiment data can be found in the work of Marx et al [18].…”
Section: Introductionmentioning
confidence: 99%